2007
DOI: 10.1159/000100833
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Clinical Significance of Prostate Cancer among 12,682 Men with Normal Digital Rectal Examination, Low PSA Levels (≤4 ng/ml) and Percent Free PSA Cutoff Values of 15 and 20%

Abstract: Aim: To report prevalence and clinical relevance of T1c prostate cancers (PCa) in a selected population of men with serum prostate-specific antigen (PSA) levels ≤4 ng/ml enrolled in a multicenter case-finding protocol. Patients andMethods: A number of 16,298 men, aged 40–75 years, from the urology units they had been referred to, in most cases (81.6%) for lower urinary tract symptoms, were evaluated. Eighty percent of them had PSA ≤4 ng/ml and about 40% PSA ≤2.5 ng/ml. Patients with PSA ≤2.5 ng/ml and PSA betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 74 publications
1
10
0
Order By: Relevance
“…In our series and in others, between 11 and 27% of PCAs with a PSA value between 2.5 and 4 ng/ml are high grade (Gleason score 6 7) [13][14][15] . Therefore, there is no PSA threshold able to differentiate between clinically significant and insignificant PCAs with both high sensitivity and high specificity [11,13,15] .…”
Section: Discussionsupporting
confidence: 69%
“…In our series and in others, between 11 and 27% of PCAs with a PSA value between 2.5 and 4 ng/ml are high grade (Gleason score 6 7) [13][14][15] . Therefore, there is no PSA threshold able to differentiate between clinically significant and insignificant PCAs with both high sensitivity and high specificity [11,13,15] .…”
Section: Discussionsupporting
confidence: 69%
“…Hence, the use of PI-RADS with multiparametric MR imaging may enable detection of clinically significant prostate cancer that could otherwise be underestimated with biopsy results. Furthermore, in a substantial number of patients with clinically significant cancer, the serum PSA level stays in the gray zone (ie, 4-10 ng/mL) or even lower (31,32). This could explain why a PI-RADS score of 4 or greater was the only significant parameter for clinically significant cancer in multivariate analysis, although all of the preoperative clinical parameters were significant in univariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In a prevalence study and clinical significance of prostate cancer among 12682 men with normal DRE and low PSA levels Pepe et al have shown that 27.4% of men with PSA between 2.5 and 4ng/mL had prostate cancer and some of them were clinically significant (19). Another recent study published by Faria et al evaluated the detection rates, clinical and pathological findings in Brazilian men with serum PSA levels <4ng/ mL.…”
Section: Discussionmentioning
confidence: 99%